IDENTIFICATION AND CLASSIFICATION OF MACULAR MORPHOLOGIC BIOMARKERS RELATED TO VISUAL ACUITY IN RADIATION MACULOPATHY: A Multimodal Imaging Study. Issue 7 (July 2020) - Parrozzani, Raffaele; Midena, Edoardo; Trainiti, Sara; Londei, Davide; Miglionico, Giacomo; Annunziata, Tommaso; Frisina, Rino; Pilotto, Elisabetta; Frizziero, Luisa
Abstract : Purpose: To identify and classify, by a multimodal imaging approach, the most relevant macular morphologic biomarkers related to visual acuity in patients affected by radiation maculopathy secondary to brachytherapy. Methods: Fifty-one consecutive patients previously treated with Iodine-125 brachytherapy because of uveal melanoma were enrolled. Each patient underwent full ophthalmologic examination including best-corrected visual acuity and multimodal macular imaging analysis. Macular morphological parameters were processed by a stepwise selection analysis. Results: Three macular parameters were identified as the most relevant macular morphologic biomarkers of poor visual acuity: the vertical thickness of the thickest macular cyst ( P = 0.0001), the presence of foveal inner segment/outer segment (IS/OS) layer disruption ( P = 0.0054), and the presence of foveal retinal pigment epithelium atrophy (0.0884). The intergrader agreement for these morphologic biomarkers was 0.98, 0.92, and 0.92, respectively (interclass correlation coefficient). Conclusion: The vertical thickness of the thickest macular cyst, the presence of foveal retinal pigment epithelium atrophy, and IS/OS layer disruption can be used to clinically characterize radiation maculopathy. These parameters allow for separation of the edematous component of radiation maculopathy, which is potentially treatable in early disease stages, from late onset atrophic components, which are theoretically irreversible. Abstract : The vertical thickness of the thickest macular cyst, the presence of foveal retinal pigment epithelium atrophy, and the presence of foveal IS/OS layer disruption are the most relevant macular morphologic parameters related to poor visual acuity in patients treated with plaque brachytherapy. These parameters allow to clinically characterize and classify radiation maculopathy.